UV–Ozone Interfacial Modification in Organic Transistors for High‐Sensitivity NO2 Detection. Issue 31 (14th June 2017) - Huang, Wei; Zhuang, Xinming; Melkonyan, Ferdinand S.; Wang, Binghao; Zeng, Li; Wang, Gang; Han, Shijiao; Bedzyk, Michael J.; Yu, Junsheng; Marks, Tobin J.; Facchetti, Antonio
Abstract : A new type of nitrogen dioxide (NO2 ) gas sensor based on copper phthalocyanine (CuPc) thin film transistors (TFTs) with a simple, low‐cost UV–ozone (UVO)‐treated polymeric gate dielectric is reported here. The NO2 sensitivity of these TFTs with the dielectric surface UVO treatment is ≈400× greater for [NO2 ] = 30 ppm than for those without UVO treatment. Importantly, the sensitivity is ≈50× greater for [NO2 ] = 1 ppm with the UVO‐treated TFTs, and a limit of detection of ≈400 ppb is achieved with this sensing platform. The morphology, microstructure, and chemical composition of the gate dielectric and CuPc films are analyzed by atomic force microscopy, grazing incident X‐ray diffraction, X‐ray photoelectron spectroscopy, and Fourier transform infrared spectroscopy, revealing that the enhanced sensing performance originates from UVO‐derived hydroxylated species on the dielectric surface and not from chemical reactions between NO2 and the dielectric/semiconductor components. This work demonstrates that dielectric/semiconductor interface engineering is essential for readily manufacturable high‐performance TFT‐based gas sensors. Abstract : Highly sensitive nitrogen dioxide gas sensors based on organic thin‐film transistors (OTFTs) having a low‐cost UV–ozone‐treated polymeric gate dielectric are fabricated. The enhanced sensing performance originates from UV–ozone‐induced hydroxylated species on the dielectric surface. This work demonstrates that simple dielectric–semiconductor interface engineering can be utilized to realize OTFT‐based gas sensors with excellent sensitivity and selectivity.